From rags to riches: three crucial steps in Dilmun’s rise to fame (poster) - Olijdam, Eric (Proceedings of the Seminar for Arabian Studies, 2014)
A myriad of cunciform texts indicate that Dilmun was one of Mesopotamia’s principal Bronze Age trading partners. In this contribution an alternative explanation will be proposed on how and when it seized control over the maritime Gulf trade at the beginning of the second millennium BC. Dilmun’s route to dominance is captured in three steps, all closely linked to key changes in its social formation process. Evidence suggests that after a formative phase, during which Bahrain was colonized and eventually became Dilmun’s core area, it took two to three generations for Dilmun to establish full control over the waters of the Lower Sea, thereby not only generating a lot of wealth but also transforming this polity into a regional superpower.